MEMS modulator to control optical system network signalling. (21st June 2011) - Mitchell, Philip; Jackson, Roger G.
MEMs technologies have evolved significantly in recent times, including MEMs designed for optical telecommunications. In many cases, MEMs components are integrated with other solid state components to realise micro opto electronic mechanical systems (MOEMS). An MEMS optical modulator has been designed utilising electrostatic operation, enabling many qualities suitable for optical network applications, including activation speed and low power consumption. MEMS geometry and analytical mode models were developed and applications performance estimated including multiphysics phenomena. Finite element analysis performed using the software suite, COMSOL®, performing static and dynamic simulations in time and frequency domains. The proposal is that the MEMS modulator is integrated with other optical components in a hermetically sealed vacuum environment, resulting in a lightly damped response with decaying oscillation. A two-step drive signal was developed and simulated using the multi-domain, simulation package SIMULINK®. The optimised MEMS design and two-step driver realised an MEMS optical modulator meeting the specification.